2019
DOI: 10.1002/jmri.26618
|View full text |Cite
|
Sign up to set email alerts
|

MRI of synovitis and joint fluid

Abstract: Synovitis and joint effusion are common manifestations of rheumatic disease and play an important role in the disease pathophysiology. Earlier detection and accurate assessment of synovial pathology, therefore, can facilitate appropriate clinical management and hence improve prognosis. Magnetic resonance imaging (MRI) allows unparalleled assessment of all joint structures and associated pathology. It has emerged as a powerful tool, which enables not only detection of synovitis and effusion, but also allows qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 107 publications
(220 reference statements)
0
29
0
3
Order By: Relevance
“…We speculate that catabolic and proinflammatory mediators triggered by synovitis lead to intra-articular debris due to cartilage breakdown. In turn, presence of articular debris causes further inflammation of the synovium [1,2,4,11]. Hypothetically, an increase in joint intra-capsular pressure could push synovitis into the subchondral bone through the cartilage defects causing the formation of BMLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that catabolic and proinflammatory mediators triggered by synovitis lead to intra-articular debris due to cartilage breakdown. In turn, presence of articular debris causes further inflammation of the synovium [1,2,4,11]. Hypothetically, an increase in joint intra-capsular pressure could push synovitis into the subchondral bone through the cartilage defects causing the formation of BMLs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported associations of knee effusion-synovitis proving that it is one of the causes of knee pain, has an adverse effect on cartilage and is linked with radiographic knee OA [3,[7][8][9][10]. Although effusion-synovitis is a significant clinical prognostic factor for OA [11], at the hip it remains under-investigated.…”
Section: Introductionmentioning
confidence: 99%
“…We have two explanations for the superiority of MRI over US for synovitis evaluation in the ankle and hindfoot region found in our study. First comes from the MRI ability to visualize the entire joint and the deep part of the synovium, irrespective of the body fat tissue amount [26], while the US can visualize only the superficial joint recesses, not necessarily involved in cases of mild joint synovitis (as were the cases with synovitis not-identified by US). Second comes from the difficulty of US to differentiate synovial hypertrophy from fluid, especially in old, long-standing effusions, when fluid becomes hypoechoic in US scan [27].…”
Section: Discussionmentioning
confidence: 99%
“…Only the use of contrast-enhanced MRI can make the distinction -the inflamed synovium enhances after contrast injection [26]. However, gadolinium administration raises the cost and duration of the MRI examination and adds considerable discomfort to the patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a one of advanced imaging techniques that play an important role in evaluating the wrist and is a useful examination modality because of its multiplanar, multisequence capability and its excellent resolution of soft tissue structures. MRI is the most sensitive imaging modality for the assessment of structures critical in the evolution of inflammatory disease, with studies confirming the superiority of MRI when compared with plain film radiography [8] The purpose of study carred out by Burke [9] was to summarize and review the role of MRI in the assessment of synovitis and joint effusion which are common manifestations of rheumatic disease and play an important role in the disease pathophysiology. MRI enables not only detection of synovitis and effusion, but also allows quantification, detailed characterization, and noninvasive monitoring of synovial processes.…”
Section: Discussionmentioning
confidence: 99%